Diversity of macrofungi (Ascomycota and Basidiomycota) in the Banyak Mountain Forest Area, Sragen District, Indonesia - VAKHA YULIA NURZAHRA; MUZAZZINAH MUZAZZINAH; METI INDROWATI (Nusantara Bioscience, 2025)
Abstract. Nurzahra VY, Muzazzinah, Indrowati M. 2025. Diversity of macrofungi (Ascomycota and Basidiomycota) in the Banyak Mountain Forest Area, Sragen District, Indonesia. Nusantara Bioscience 16: 39-48. Macroscopic fungi are high-value forest components that play an essential functional role in forest ecosystems. However, studies focusing on the diversity of macroscopic fungi in Indonesian forests are still limited and underexplored. The forest located in Banyak Mountain is one example of a forest area in Indonesia that has significant macroscopic fungal diversity. This study aims to examine the diversity of macroscopic fungi species in the Banyak Mountain Forest Area, Sragen District. The research employed an exploratory method by establishing 2×2 m plots using purposive sampling techniques and conducting descriptive analyses of the collected data. The results of the study in the Banyak Mountain Forest Area identified 33 species of macroscopic fungi from two divisions, namely Basidiomycota and Ascomycota, which are classified into four classes, six orders, twelve families, and twenty-two genera. Most macroscopic fungi found were substrate-dependent on decayed wood, with fewer species located on the soil. The environmental factors influencing their growth include air temperatures ranging from 28 to 32°C, air humidity between 67 and 80%, and soil pH levels of approximately 6.0 to 7.5, which are highly conducive to fungal proliferation. These findings provide a valuable checklist for future research on fungal distribution in tropical regions and contribute significantly to biodiversity conservation efforts.